ANALISIS PENGARUH USABILITY, REPUTASI DAN KEAMANAN TERHADAP KEPERCAYAAN MASYARAKAT DALAM BERTRANSAKSI MENGGUNAKAN E-MONEY DI INDONESIA - Marsyel Thixman; Kartika Gianina Tileng (AITI, 2016)
E-Money is an instrument of non-cash transaction or payment instrument without the physical presence of the money. E-Money is saving the amount of money into the electronic equipment, which is then used to perform a transaction. Along the development, E-Money is increasingly being used in Indonesia. Therefore, the researchers will conduct an analysis to know if there is a significant effect of the factors such as usability, reputation and security to public confidence in Indonesia to conduct the transactions using E-Money. The purpose of this study is to determine: (a) Does the factor of usability have a significant positive effect to public confidence in Indonesia to do the transactions by using E-Money, (b) Does the factor of reputation have a significant positive effect to public confidence in Indonesia to do the transactions by using E-Money (c) Does the factor of safety have a significant positive effect to public confidence in Indonesia to do the transactions by using E-Money, (d) other matters that could have a significant effect to public confidence in Indonesian to do the transactions by using E-Money. The respondents in this study will be drawn randomly to the people who have been using E-Money as an instrument of the transactions. This research was conducted by using Path Analysis after previously doing normality testing, validity testing, and reliability testing. The results of this study prove that: (1) the existence of a significant positive effect of reputation to public confidence in using E-Money (2) the existence of a significant positive effect of a security to public confidence in using of E-Money (3) the existence of a significant positive effect of a reputation to public confidence in using of E-Money (4) the existence of a significant positive effect of a usability to reputation in using of E-Money (5) the existence of a significant positive effect of a usability to security in using of E-Money. This study also serves to provide input to the various parties, such as the vendors of E-Money developers, community as the users and potential users of E-Money, as well as the students and academics who are interested in studying E-Money. This research models is good because the results is significant between variable as a hypothesis.